2000
DOI: 10.1073/pnas.050583297
|View full text |Cite
|
Sign up to set email alerts
|

Castration increases and androgens decrease nitric oxide synthase activity in the brain: Physiologic implications

Abstract: Sex differences in nitric oxide synthase (NOS) activity in different regions of the rat brain and effects of testosterone and dihydrotestosterone (DHT) treatment in orchidectomized animals were investigated. Regional but no sex differences in NOS activity were detected in gonadectomized animals. Orchidectomy significantly increased NOS activity in the hypothalamus, ''amygdala,'' and cerebellum but not in the cortex. In the hypothalamus, the increase in NOS activity after castration and its reversal by androgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…In female, but not male brain, loss of NO through targeted gene deletion or pharmacological inhibition increases ischemic damage and renders neurons insensitive to the neuroprotection ordinarily provided by an important female sex steroid, 17b estradiol. These observations are not explained by compensatory upregulation of other NOS isoforms as can occur with hormone exposure, (Singh et al, 2000;Hayashi et al, 1997;Garcia-Duran et al, 1999;Dimmeler et al, 2000;Grohe et al, 2004) preservation of ischemic CBF. Second, PARP-1's importance in ischemic neuronal death is also sexually dimorphic.…”
Section: Discussionmentioning
confidence: 78%
“…In female, but not male brain, loss of NO through targeted gene deletion or pharmacological inhibition increases ischemic damage and renders neurons insensitive to the neuroprotection ordinarily provided by an important female sex steroid, 17b estradiol. These observations are not explained by compensatory upregulation of other NOS isoforms as can occur with hormone exposure, (Singh et al, 2000;Hayashi et al, 1997;Garcia-Duran et al, 1999;Dimmeler et al, 2000;Grohe et al, 2004) preservation of ischemic CBF. Second, PARP-1's importance in ischemic neuronal death is also sexually dimorphic.…”
Section: Discussionmentioning
confidence: 78%
“…Many of the actions of E2 on the brain have been suggested to be through an NOmediated mechanism (54,55). Castration increases and androgen treatment decreases nNOS activity in the brain (56). Immunohistochemical studies from our laboratory also revealed co-localization of nNOS and ERα in the subfornical organ of female mice (57).…”
Section: Nitric Oxide and Sex Differencesmentioning
confidence: 78%
“…However, similar studies in mice, especially involving the striatum, are lacking. It should be mentioned that the literature on this topic is rather confusing; for instance, studies focusing on the neuroendocrine system have shown that the activity of neuronal NOS is increased by estrogen (36) and decreased by androgens (37). In any case, if these influences were present at the level of the nigrostriatal system, they could possibly account for the differential sensitivity of female mice to the 'anticataleptic' effect of NO donors.…”
Section: Influence Of Gender On Central Nitrergic Transmissionmentioning
confidence: 99%